Metabolic aspects of palladium(II) potential anti-cancer drugs - Carneiro, Tatiana J. (2021)
This mini-review reports on the existing knowledge of the metabolic effects of palladium [Pd(II)] complexes with potential anticancer activity, on cell lines and murine models. Most studies have addressed mononuclear Pd(II) complexes, although increasing interest has been noted in bidentate complexes, as polynuclear structures. In addition, the majority of records have reported in vitro studies on cancer cell lines, some including the impact on healthy cells, as potentially informative in relation to side effects. Generally, these studies address metabolic effects related to the mechanisms of induced cell death and antioxidant defense, often involving the measurement of gene and protein expression patterns, and evaluation of the levels of reactive oxygen species or specific metabolites, such as ATP and glutathione, in relation to mitochondrial respiration and antioxidant mechanisms. An important tendency is noted toward the use of more untargeted approaches, such as the use of omic sciences e.g., proteomics and metabolomics. In the discussion section of this mini-review, the developments carried out so far are summarized and suggestions of possible future developments are advanced, aiming at recognizing that metabolites and metabolic pathways make up an important part of cell response and adaptation to therapeutic agents, their further study potentially contributing valuably for a more complete understanding of processes such as biotoxicity or development of drug resistance.